Faktor Penyebab Rendahnya Pelaporan Insiden Keselamatan Pasien - Momen Amalia (Vitalitas Medis : Jurnal Kesehatan dan Kedokteran, 2024)
Incident reporting is the starting point in a patient safety program. Reposrting patient safety incident at RSUP Dr. tadjuddin Chalid Makassar accured an increase from 9 reports in 2019 and 11 reportis in 2021. This means that awareness of reporting patient safety incidents is still lacking at RSUP Dr. Tadjuddin Chalid Makassar. Research purposes: the aim of this research wa to find out what the casual factors are low reporting in patient safety incidents at RSUP Dr. Tadjuddin Chalid Makassar. Method: this study a quantitative method whit a cross design sectional. sampling technique using total sampling. respondens on this study amounted to 102 nuses. Results and Discussion: The results of the study showed that there was no relationship between knowledge and low reporting in patient safety incidents (p = 0.277 ≥ 0.05) was due many nurses did not know how to report, feelings will be afraid of being blamed, and there was is no relationship between rewards and low reporting of patient safety incidents (p = 0.188 ≥ 0.05) because the hospital has not implemented a reward system and there is a relationship between motivation and low reporting of patient safety incidents (p = 0.48 < 0.05),66 indicating that nurses have strong motivation to report reporting patient safety incidents. Suggestion: It is hoped that hospitals can increase the knowledge of nurses to remain consistent in reporting patient safety incidents and hospital leaders must support activities or programs that lead to patient safety.